Soil priorities in the European Union - Panagos, Panos; Montanarella, Luca; Barbero, Mirco; Schneegans, Annette; Aguglia, Laura; Jones, Arwyn (Geoderma Regional, 2022)
Soils provide crucial ecosystem services such as the provision of food, carbon sequestration and water purification. Soil is the largest terrestrial pool of carbon, hosts more than 25% of all biodiversity and provides 95–99% of food to 8 billion people. The European Union (EU) puts the concept of healthy soils at the core of the European Green Deal to achieve climate neutrality, zero pollution, sustainable food provision and a resilient environment. Given the European Union's objective to become the first climate neutral continent by 2050, the European Commission adopted a series of communications for a greener Europe. In 2020, an ambitious package of measures were presented within the Biodiversity 2030, Farm to Fork and Chemicals Strategies, as well as the Circular Economy Action Plan and the European Climate Law, which included actions to protect soils (Montanarella and Panagos, 2021). In 2021, these were followed by the Fit for 55 package, the Zero Pollution Action Plan and the EU Soil Strategy for 2030. All these policies include provisions relevant to soils to achieve the ambitious objectives of the EU Green Deal. •The European Union puts the concept of healthy soils at the core of the European Green Deal.•Healthy soils contribute to achieve climate neutrality, zero pollution, sustainable food provision and resilient environment.•70% of EU soils are in an unhealthy condition with erosion, carbon loss, land take and contamination being major threats.•EU Soil Strategy for 2030 targets to have all EU soil ecosystems in a healthy condition by 2050.•The EU Soil Observatory supports the implementation of relevant EU policies (EU Soil Strategy 2030, CAP, Zero Pollution).